Constitutive active/androstane receptor, peroxisome proliferator-activated receptor α, and cytotoxicity are involved in oxadiazon-induced liver tumor development in mice. (February 2016) - Kuwata, Kazunori; Inoue, Kaoru; Ichimura, Ryohei; Takahashi, Miwa; Kodama, Yukio; Yoshida, Midori
Abstract: Oxadiazon (OX) is a protoporphyrinogen oxidase-inhibiting herbicide that induces porphyria and liver tumors in rodents. Although porphyria is generally considered to be a risk factor for liver tumor development, the mechanisms through which OX mediates tumor development are unclear. Therefore, in this study, we investigated the mechanisms of tumor development by focusing on constitutive active/androstane receptor (CAR), which is essential for the development of tumors in response to several chemicals. After 1, 4, or 13 weeks of dietary treatment with 1000 ppm OX, hepatic Cyp2b10 expression was induced in wild-type (WT) mice. However, this effect was blocked in CAR-knockout (CARKO) mice. Hepatic Cyp4a10 expression, indicative of peroxisome proliferator-activated receptor α (PPARα) activation, and cytotoxic changes in hepatocytes were also observed in both groups of mice. After initiation by diethylnitrosamine, 26-week treatment with OX resulted in an increase in proliferative lesions, including foci and adenomas, in both genotypes, and the incidence and multiplicity of proliferative lesions in CARKO mice were higher than those in control mice but lower than those in WT mice. These results suggested that CAR, PPARα activation, and cytotoxicity were involved in the development of liver tumors. Moreover, porphyrin was not apparently involved in OX-induced tumor development. Highlights: OX induces porphyria, which is generally a risk factor for liver tumors. We investigated the mechanism of OX-induced liver tumor development in CARKO mice. No pathological porphyrin deposition was observed in the livers. CAR was involved in the development of OX-induced liver tumors. PPARα activation and cytotoxicity may be involved in OX-induced liver tumors.